HADIS DAN SUNAH DALAM PERSPEKTIF IGNAZ GOLDZIHER - Rohmansyah (Al-Majaalis : Jurnal Dirasat Islamiyah, 2015)
Hadith and Sunah is a staple source of Islamic teachings which serve as explanatory against the verses of the Qur'an. But in reality there is still some Orientalist Ignaz Goldziher i.e. makes a statement with distinguishing between Hadith and Sunah which differ with the opinion of the experts of Hadith and Fiqh. This article will try to explain the Hadith and sunah according to Ignaz Goldziher theory of hermeneutics Dasein Heidegger and use methods of analysis-interpretation approach. From here will be revealed how a biography of Ignaz Goldziher, thoughts and opinions of the scholars of Hadith or Fiqh related Hadith and sunah, then the implications in the study of Islamic thought is the Hadith and Sunah.